THE DEVELOPMENT OF SCIENCE FICTION AS A LITERARY GERNE - Yuldasheva Mahinur Baxodir qizi; ABDURAMONOVA DIANA VALERYEVNA (TADQIQOTLAR.UZ, 2024)
Abstract: Numerous historical, cultural, and technological developments have influenced the evolution of science fiction as a literary genre. Science fiction first appeared in the 19th century as a speculative examination of scientific discoveries and their possible repercussions, as seen by works such as Mary Shelley’s *Frankenstein* and H.G. Wells’ *The War of the Worlds*. The genre developed into a variety of subgenres, including cyberpunk, dystopian fiction, and space opera, as a result of changes in society, politics, and science over time. The genre began to explore questions of identity, morality, and the human condition in a world that was becoming more complex, rather than just picturing futuristic technologies.